PENYERAPAN LOGAM Pb DENGAN MENGGUNAKAN KARBON AKTIF DARI CANGKANG KEMIRI SEBAGAI ADSORBEN - Supraptiah, Endang; Ningsih, Aisyah Suci; ., Fatria (Politeknik Negeri Sriwijaya, 2014)
Candlenut shell is a waste which usually burned, stacked or discarded,which are unfavorable to environment. This is condition be motivated to produced commercial product from this candlenut shells waste as activated carbon and aswell as solving as environment problems.This study aimed is to obtain the optimum conditions of hydrochloric acid activator to quality activated carbon and Pb metal adsorption capacity. This activated carbon has two variation process there are carbonization process used temperature 500oC for 1 hour and the activation process with variation concentration of hydrochloric acid there are 0,2M, 0,4M, 0,6M, 0,8M and 1M for 24 hours. The product of this research isshowing the best quality activated carbon from candlenut shells which has best characteristic or fit to SNI 06-3730-95 such as to Inherent Moisture rate 8,54-10,56%, ash content 1,10-2,48%, volatile matter 17,57-20,63% and fixed carbon 67,81-71,42%. The application of activated carbon from candlenut shell can reduce the Pb metal concentration from 3 ppm to 0 ppm with activator concentration 0,4M for contact time of 1 hour with adsorption content is 100% and adsorption capacity of activated carbon from candlenut shell using hydrochloric acid as adsorbent Pb metal is 0,15 mg/g.